2016
DOI: 10.9734/ajea/2016/25447
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Foliar Application of Growth Regulators and Micronutrients on the Performance of Darjeeling Mandarin

Abstract: Investigation was carried out in the farmer's field of Kalimpong to evaluate the effect of foliar application of different level of GA 3 and micronutrients on Darjeeling mandarin. The experimental design was adopted randomized block design in which there was seven main plot treatments representing combinations of three growth regulators (GA

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 21 publications
4
7
0
Order By: Relevance
“…The above findings are supported by Gurung et al (2016) in mandarin.The increase in the sugar content might be due to the more rapid translocation of sugars from leaves to developing fruits. Boron facilitated sugar transport within the plant.…”
Section: Reducing Sugarssupporting
confidence: 69%
“…The above findings are supported by Gurung et al (2016) in mandarin.The increase in the sugar content might be due to the more rapid translocation of sugars from leaves to developing fruits. Boron facilitated sugar transport within the plant.…”
Section: Reducing Sugarssupporting
confidence: 69%
“…These results were coincide with those obtained by Dawoodet al 2000 Gurung et al (2016). They concluded that foliar spraying of micronutrients (boron and zinc) increased the yield and the combined spraying of them was most effective in improving the fruit yield / tree in citrus and other fruit crops.…”
Section: Effect Of Multi-micronutrient and Putruscine Application Alosupporting
confidence: 90%
“…With respect to fruit quality upon harvest, Dawood et al (2000), EL-Baz (2003), Hafez and El Metwally (2007), Tariq et al (2007), Abd El-Motty et al (2010), Hanafy Ahmed et al (2012), Sarrwy et al(2012) Abd El-Motty and Orabi (2014), Salama (2015) and Gurung et al (2016) found that spraying micronutrients (boron and zinc) have important role in fruit quality improvement in citrus and other fruit crops. Also, Khan et al (2012) and Baghdady et al (2014) indicated that foliar spraying with Chelated zinc and boron significantly increased fruit quality in orange and madarin fruits.…”
Section: B Fruit Chemical Content: 1 Total Soluble Solids (Tss)tssmentioning
confidence: 99%
“…The increased TSS due to the spray of nutrients combination might be due to the increased photosynthesis activity [25], translocation of sugars from source to sink and conversion of complex form of sugars (polysaccharides) to simple sugars (glucose and fructose) in fruits [21] due to the increased activities of enzymes by zinc and potassium. The results of present study are supported by the findings of investigators who reported the highest total soluble solids in Kinnow mandarin with foliar application of GA 3 15 ppm along with zinc 0.5% and boron 0.1% [26]. Researchers stated that Kinnow mandarin fruits had the highest total soluble solids with foliar application of Zn + B on plants [27].…”
Section: Chemical Parameterssupporting
confidence: 89%